A qualitative exploration of facilitators and inhibitors influencing nurses' intention to leave clinical nursing - Leyla Alilu; Leila Valizadeh; Vahid Zamanzadeh; Hosein Habibzadeh; Mark Gillespie
Abstract OBJECTIVE The aim of this study was to determine the barriers and facilitators shaping the development of an intent to leave the nursing profession, from the perspective of Iran's clinical nurses. METHOD The study was completed using qualitative content analysis And included 21 Participants who were clinical nurses with a variety of work experience across a range of clinical posts. Semi-structured interviews were used to collect data and data obtained from the interviews were analyzed and interpreted utilizing a content analysis method. RESULTS During data analysis, 2 main themes, 5 categories and 12 subcategories were extracted as follows. Facilitators include: (I) spoiled identity (weak social status and violation of dignity), (II) frustration (feeling subordinate including a lack of appreciation), and (III) experience of hard labor (job stress, hard work and shift work). Inhibitors include: (I) positive management behaviors (rewards and support systems), and (II) being valuable (spiritual satisfaction, the efficient presence and professional capabilities development). CONCLUSION Based on the findings, it can be concluded that managers can prevent nurses from leaving clinical nursing by providing appropriate activities for them and increasing their motivation and satisfaction.